233k views
3 votes
Plz Simplify using i. √-15√-4

User Niroj
by
5.0k points

1 Answer

4 votes

Explanation:


√(ab)=√(a)\cdot√(b)\\\\√(-15)\cdot√(-4)=√((-15)(-4))=√(60)=√((4)(15))=\sqrt4\cdot√(15)=2√(15)


\text{If the examples are separate.}\\\\√(-1)=i\\√(ab)=√(a)\cdot√(b)\\\\√(-15)=√((15)(-1))=√(15)\cdot√(-1)=√(15)\ i\\\\√(-4)=√((4)(-1))=\sqrt4\cdot√(-1)=2i

User Rob Hogan
by
6.0k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.